The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1177/0194599811425019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Factors Concerning the Olfaction Using the Sniffin’ Sticks Test

Abstract: This is the first study that evaluated the relationship between education level and olfaction. According to the results, the cultural differences, education level, and age seemed to influence odor scores. The Sniffin' Sticks test can be used to assess olfactory performance in a Turkish population, but identification of odors in this test battery may show variability because of local and cultural factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 27 publications
2
39
1
2
Order By: Relevance
“…However, several previous studies found no significant effect of gender on olfactory function (2,16,21). Moreover, Robinson et al (22) reported that increasing levels of beta-estradiol had no effect on olfactory thresholds.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, several previous studies found no significant effect of gender on olfactory function (2,16,21). Moreover, Robinson et al (22) reported that increasing levels of beta-estradiol had no effect on olfactory thresholds.…”
Section: Discussionmentioning
confidence: 94%
“…Olfactory function was slightly better in non-smokers than in smokers; however, the difference was not statistically significant. In a study of 100 healthy individuals, Orhan et al (16) found no association between olfactory function and smoking or gender. However, although smoking does not consistently affect smell test scores, it is widely believed to Turk Arch Otorhinolaryngol 2015; 53: 4-9…”
Section: Discussionmentioning
confidence: 95%
“…The SS test has been used previously to assess olfactory performance in a Turkish population, but the odor identification results obtained using this test may vary due to local and cultural factors (16,17). We evaluated the olfactory function of BD patients using this test.…”
Section: Discussionmentioning
confidence: 99%
“…The most common ones are: the University of Pennsylvania Smell Identification Test, the Connecticut Chemosensory Clinical Research Center Test, and the Sniffin’ Sticks Test 11. The Sniffin’ Sticks Test is available for olfactory assessment in Turkey, Europe, and Australia 11.…”
Section: Introductionmentioning
confidence: 99%
“…The most common ones are: the University of Pennsylvania Smell Identification Test, the Connecticut Chemosensory Clinical Research Center Test, and the Sniffin’ Sticks Test 11. The Sniffin’ Sticks Test is available for olfactory assessment in Turkey, Europe, and Australia 11. It is a well-designed olfactory test that the German Olfactology and Gustology Association12 recommends and uses in many studies that assess the olfactory functioning of MS patients.…”
Section: Introductionmentioning
confidence: 99%